IR‐ATR Chemical Sensors Based on Planar Silver Halide Waveguides Coated with an Ethylene/Propylene Copolymer for Detection of Multiple Organic Contaminants in Water1. Issue 8 (1st February 2013) - Lu, Rui; Sheng, Guoping; Li, Wenwei; Yu, Hanqing; Raichlin, Yosef; Katzir, Abraham; Mizaikoff, Boris
<x xml:space="preserve">Abstract</x> Sensitive: Several monocyclic aromatic hydrocarbons, for example p‐, m‐, o‐xylene, toluene, and benzene (1–5), were detected in a single measurement by using a planar infrared attenuated total reflection (IR‐ATR) fiberoptic sensor that was coated with ethylene/propylene copolymer. Compared to conventional IR sensing systems, this device exhibits a large dynamic detection range.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>